WASTE OF FLOUR HOUSES OF ALAGOAS STATE: USE AND PERSPECTIVES - Souza, S. de O.; da Silva, A. P. B.; da Silva, R. M.; de Oliveira, L. C.; Goveia, D.; Botero, W. G. (Revista Brasileira de Engenharia de Biossistemas, 2015)
The Brazil is one of the largest agricultural producers in the world, among the various types of farming, cassava is considered one of the main, because the use of almost all parts of this plant. It is a food grade product both for humans and for animals. However, it is observed in this case a high production of waste that can generate damage to the environment and society, including because of its toxicity. Such waste should be highlighted the cassava peel and Manipueira. Manipueira is a liquid light yellow color resulting from the pressing of the mass of cassava. This work demonstrated that these sub-products have considerable levels for macro, micronutrients and organic matter, and may present several applications, among them the use to supplement in animal feed and especially in soil application as fertilizer, in different cultures, generating income, thus reducing costs and minimizing damage to the environment has been drawing.